Differential prevalence and risk factors for infection with coronaviruses in bats collected from Yunnan Province, China - Ruiya Li; Alexander Tendu; Yakhouba Kane; Victor Omondi; Jiaxu Ying; Lingjing Mao; Shiman Xu; Rong Xu; Xing Chen; Yanhua Chen; Stéphane Descorps-Declère; Kathrina Mae Bienes; et al. (One Health)
Coronaviruses (CoVs) pose a threat to human health globally, as highlighted by severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS) and the COVID-19 pandemic. Bats from the Greater Mekong Subregion (GMS) are an important natural reservoir for CoVs. Here we report the differential prevalence of CoVs in bats within Yunnan Province across biological and ecological variables. We also show the coexistence of CoVs in individual bats and identify an additional putative host for SARS-related CoV, with higher dispersal capacity than other known hosts. Notably, 11 SARS-related coronaviruses (SARSr-CoVs) were discovered in horseshoe bats (family Rhinolophidae) and a Chinese water myotis bat (Myotis laniger) by pan-CoV detection and Illumina sequencing. Our findings facilitate an understanding of the fundamental features of the distribution and circulation of CoVs in nature as well as zoonotic spillover risk in the One health framework.